Placental mitochondrial adaptations in preeclampsia associated with progression to term delivery. Issue 12 (December 2018) - Holland, Olivia; Cuffe, James; Dekker Nitert, Marloes; Callaway, Leonie; Kwan Cheung, Keith; Radenkovic, Filip; Perkins, Anthony
Abstract Preeclampsia is a devastating pregnancy disorder. Severity varies widely, and while severe preeclampsia often requires pre-term delivery, women with mild preeclampsia may reach term with minor interventions. The mechanisms that mediate disease severity are poorly understood, but may include adaptive processes by the placenta. We aimed to establish whether in pregnancies that reached term and those that delivered pre-term, the placental response to preeclampsia was intrinsically different, and explore potential adaptive mechanisms. Hydrogen peroxide production and antioxidant activity were increased in term preeclamptic placentae, whereas pre-term preeclamptic placentae had reduced hydrogen peroxide production and reduced function of the antioxidant system superoxide dismutase compared to control placentae. Markers of mitochondrial fission/fusion, apoptosis and the expression level of mitochondrial complexes were differentially disrupted in term compared to pre-term preeclamptic placentae. Mitochondrial respiration and content were increased in term preeclamptic placentae, but mitochondria had a lower respiratory reserve capacity. Mitochondrial respiration and hydrogen peroxide production were increased in healthy term placentae after in vitro hypoxia/reoxygenation. Placentae from preeclamptic pregnancies that reached term showed multiple adaptions that were not present in pre-term preeclamptic placentae. Increased antioxidant activity, and expression of markers of mitochondrial fusion and apoptotic suppression, may relate to salvaging damaged mitochondria. Increased mitochondrial respiration may allow ongoing tissue function even with reduced respiratory efficiency in term preeclamptic pregnancies. Response after in vitro hypoxia/reoxygenation suggests that disruption of oxygen supply is key to placental mitochondrial adaptations. Reactive oxygen species signalling in term preeclamptic placentae may be at a level to trigger compensatory antioxidant and mitochondrial responses, allowing tissue level maintenance of function when there is organelle level dysfunction.